Historiografi Islam - Primawan, Dini Pandu; Mawardi, Kholid (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In pre-Islamic times, the Arab people did not record the historical events they experienced; instead, they relied on memorization and oral traditions to preserve information related to their history. As time progressed, Islamic historiography emerged in the writing of Islamic history. Based on what has been stated, the author tends to write about Islamic historiography. This research is a type of library research. The analysis is conducted by collecting, exploring, and focusing on the substance of Islamic historical data related to the development of Islamic historiography. In its development, Islamic historiography consists of several stages or periods, namely the early stage, middle stage, early modern stage, and modern stage. Each stage has its own prominent figures. Moreover, in the writing of Islamic history, various polemics exist, including those related to the credibility of sources, differences in perspectives and interpretations, and the use of history for political purposes. Through Islamic historiography, historians are able to identify important events in Islamic history that have influenced the development of political and social culture, the effects of which can still be felt today. Keywordss : historiography, islam, history.